The protoplanetary disc HD 163296 as observed by ALMA - P.N. Diep; D.T. Hoai; N.B. Ngoc; P.T. Nhung; N.T. Phuong; T.T. Thai; P. Tuan-Anh (Vietnam Journal of Science, Technology and Engineering, 2022)
HD 163296 is one of the few protoplanetary discs displaying rings in the dust component. The present work uses ALMA observations of the 0.9 mm continuum emission, which have significantly better spatial resolution (~8 au) than previously available, to provide new insight into the morphology of the dust disc and its double ring structure. The disc is shown to be thin, and its position angle and inclination with respect to the sky plane are accurately measured as are the locations and shapes that characterise the observed ring-gap structure. Significant modulation of the intensity of the outer ring emission is revealed and discussed. In addition, earlier ALMA observations of the emission of three molecular lines, CO(2-1), C18O(2-1), and DCO+(3-2) with a resolution of ~70 au are used to demonstrate the Keplerian motion of the gas, which is found to be consistent with a central mass of 2.3 solar masses. An upper limit of ~9% of the rotation velocity is placed on the in-fall velocity. The beam size is shown to give the dominant contribution to the line widths, accounting for both their absolute values and their dependence on the distance to the central star.